2012
DOI: 10.3758/s13415-012-0115-9
|View full text |Cite
|
Sign up to set email alerts
|

Intact risk-based decision making in rats with prefrontal or accumbens dopamine depletion

Abstract: The medial prefrontal cortex (mPFC) and the core region of the nucleus accumbens (AcbC) are key regions of a neural system that subserves risk-based decision making. Here, we examined whether dopamine (DA) signals conveyed to the mPFC and AcbC are critical for risk-based decision making. Rats with 6-hydroxydopamine or vehicle infusions into the mPFC or AcbC were examined in an instrumental task demanding probabilistic choice. In each session, probabilities of reward delivery after pressing one of two available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…At the same time, studies that have explicitly examined the role of dopamine levels in experiments involving time trade‐offs have failed to find that such dysregulation impacts decision‐making. For example, it has been shown that depletion of local dopamine levels in the NAc does not affect time‐discounting judgments in decision‐making tasks (Winstanley et al ., ) and nor does it affect decision‐making in other settings (Walton et al ., ; see also Mai & Hauber, ). This finding is difficult to reconcile with the proposition that the critical role of vHC/NAc interaction in the deficits that we observed is in the regulation of dopamine.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…At the same time, studies that have explicitly examined the role of dopamine levels in experiments involving time trade‐offs have failed to find that such dysregulation impacts decision‐making. For example, it has been shown that depletion of local dopamine levels in the NAc does not affect time‐discounting judgments in decision‐making tasks (Winstanley et al ., ) and nor does it affect decision‐making in other settings (Walton et al ., ; see also Mai & Hauber, ). This finding is difficult to reconcile with the proposition that the critical role of vHC/NAc interaction in the deficits that we observed is in the regulation of dopamine.…”
Section: Discussionmentioning
confidence: 90%
“…The first five sessions ensured that the rats learned the response–outcome contingency at a given probability through experience. This experience occurred through a high number of ‘forced choice’ trials for each probability (30 in total, 15 per stimulus; see ), so that the animal could accurately estimate the probability of reward given its infrequent occurrence (see also, Mobini et al ., ; Nasrallah et al ., , ; Mai & Hauber, ). Thus, unlike previous studies that include few forced choice trials irrespective of probability (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, infusion of D1 antagonists into the NAC of rats decreases the preference for larger, uncertain rewards on a probability discounting task. In contrast, infusion of a D1 or D2/D3 agonists into the NAC i ncreases risk preference when reward probability is high (Norbury et al, 2013; Stopper et al, 2013; however, see Mai and Hauber, 2012). Infusion of D1 agonists into the NAC may also “optimize” decision making in treated animals as one study reported that treated rats were more likely to choose the large and uncertain reward when reward probability was high, but were more likely to avoid this option when probabilities were low (Stopper et al, 2013).…”
Section: Neural Systems Involved In Setting the Preference For Riskmentioning
confidence: 99%
“…Furthermore, increases in dopamine concentration are associated with increased risk preference in humans (Zack and Poulos, 2004; Dodd et al, 2005; Dang et al, 2011) and rodents (St. Onge and Floresco, 2009; Stopper et al, 2013). Finally, stimulation of dopamine D1 receptors within the NAC enhances risk preference (Stopper et al, 2013; however, see Mai and Hauber, 2012). Consequently, we propose that effort-induced increases in NAC dopamine concentration drives risk preference by enhancing dopamine release in the NAC.…”
Section: How Does Effort Alter Risk Preference?mentioning
confidence: 99%